Rapid Genetic Divergence of an Invasive Species, Spartina alterniflora, in China - Xia, Lu; Geng, Qifang; An, Shuqing (Frontiers in Genetics, 2020)
Spartina alterniflora, which were collected from North Carolina, Georgia, and Florida, were introduced to China in 1979. However, according to documented records, S. alterniflora from different origins were introduced to different areas when the species was first introduced to the coastal areas of China in the 1980s. A total of 715 samples of S. alterniflora were collected from nine invasive populations in China and nine native populations from the United States. The genetic diversity and genetic structure of invasive and native populations were compared using microsatellite markers. The heterozygosity of invasive populations of S. alterniflora were similar with those of native populations, which may attribute to its multiple introductions from different geographic areas of USA. However, the lower allelic diversities of invasive populations were detected, which may be due to the founder effect, or the bottleneck. The results of the STRUCTURE analysis among all sampling sites showed that the value of ΔK was largest when K = 2, which indicated that the invasive S. alterniflora populations in China had completed differentiated from the native populations of USA. This may be because of admixture and hybridization of three original populations, or the the post-introduction rapid evolution in China. Significant genetic structure (K = 7) and high genetic differentiantion (Fst = 0.30193) were detected in invasive populations, which may due to the low natural gene flow among populations. The genetic structure of the populations in China was still affected by the human-mediated introductions in the 1980s, and the different initial introductions might promote differentiation among the invasive populations. Multi-source introductions of S. alterniflora is perhaps helpful for local adaptation but itself can’t cause rapid spread along the whole coastal China, and the human-mediated long-distance dispersal should take the most of responsibility for the rapid spread of S. alterniflora. Meanwhile, we suggest that the prevention of gene exchange among populations of S. alterniflora is the first and most important step in the control of the species on the coast of China, because admixture and hybridization of isolated populations might generate new heterosis and increase the difficulty of managing S. alterniflora in China.